Breeding of cassava for low cyanogenic potential: problems, progress and prospects - Dixon, A.; Asiedu, Robert; Bokanga, M. (International Society for Horticultural Science, 1994)
The starchy staples of cassava (tuberous roots) provides more than half the calories consumed by more than 200 million people in sub-Saharan Africa, and the leaves are often used as a vegetable providing protein, vitamins and minerals. The cyanogenic potential of cassava has often been cited as a causal factor of health problems, particularly in areas where cassava roots are not properly processed. Provision of improved genotypes with low cyanogenic potential would ameliorate these problems. Breeding of cassava for low cyanogenic potential has been a high priority of the Root and Tuber Improvement Program at the International Institute of Tropical Agriculture since its inception. This paper discusses the role of IITA in breeding for low cyanogenic potential, and addresses problems, progress and future strategies.